Quantitative analysis of the polymeric blends. Issue 2 (May 2019) - Kisiel, Maciej; Mossety-Leszczak, Beata; Frańczak, Agnieszka; Szczęch, Dominik
A method of quantitative analysis of polypropylene/linear low density polyethylene blends was determined by using differential scanning calorimetry. The samples were prepared by means of extrusion process. The method of quantitative analysis was based on the principle that the melting enthalpies of the components in the mixture are proportional to their amount, but it has been found that the presence of two polymers in the blend has influence on the crystallization of its components. Previous studies seemed to neglect this phenomenon, so a linear correlation allowing to eliminate discrepancies between calculated and actual quantitative blend composition has been developed. This approach was proven to be more accurate than earlier directly proportional enthalpy—quantity dependence.